A comparison of sunlight exposure in men with prostate cancer and basal cell carcinoma - Rukin, N J (Nature Publishing Group, 2007)
Ultraviolet radiation exposure increases basal cell carcinoma (BCC) risk, but may be protective against prostate cancer. We attempted to identify exposure patterns that confer reduced prostate cancer risk without increasing that of BCC. We used a questionnaire to assess exposure in 528 prostate cancer patients and 442 men with basal cell carcinoma, using 365 benign prostatic hypertrophy patients as controls. Skin type 1 (odds ratio (OR)=0.47, 95% CI=0.26–0.86), childhood sunburning (OR=0.38, 95% CI=0.26–0.57), occasional/frequent sunbathing (OR=0.21, 95% CI=0.14–0.31), lifetime weekday (OR=0.85, 95% CI=0.80–0.91) and weekend exposure (OR=0.79, 95% CI=0.73–0.86) were associated with reduced prostate cancer risk. Skin type 1 (OR=4.00, 95% CI=2.16–7.41), childhood sunburning (OR=1.91, 95% CI=1.36–2.68), regular foreign holidays (OR=6.91, 95% CI=5.00-9.55) and weekend (OR=1.17, 95% CI=1.08–1.27) but not weekday exposure were linked with increased BCC risk. Combinations of one or two parameters were associated with a progressive decrease in the ORs for prostate cancer risk (OR=0.54–0.25) with correspondingly increased BCC risk (OR=1.60–2.54). Our data do not define exposure patterns that reduce prostate cancer risk without increasing BCC risk.